Viabilidade econômica de sistemas fotovoltaicos no Brasil e possíveis efeitos no setor elétrico - Stefano Giacomazzi Dantas; Fabiano Mezadre Pompermayer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This work discusses the economic viability of photovoltaic systems usage in distributed generation of electricity and its possible impacts on electrical network. We present the current situation and perspectives of distributed generation in Brazil. Besides that, we developed a financial analysis of grid-tie photovoltaic systems, considering factors such as local solar radiation and conventional energy cost, using data from the National Agency of Electrical Energy (ANEEL). Overall, the usage of photovoltaic systems in Brazil is economically attractive. Despite this, we have to discuss the impacts on the electrical network that might happen due to energy supply variability and economic losses of electric companies and users. However, we show that there is still a lot of room for development of photovoltaic systems in Brazil, especially within regions with high solar radiation.
Keywords: Q42; Q48; 330; photovoltaic solar energy; tariff policy